Effects of Flavin-Goethite Interaction on Goethite Reduction by Shewanella decolorationis S12 - Zhao, Gang; Li, Enze; Li, Jianjun; Liu, Fei; Yang, Xunan; Xu, Meiying (Frontiers in Microbiology, 2019)
Flavin mononucleotide (FMN) and riboflavin are structurally similar flavins, except for the presence of a phosphate group on the FMN molecule. They are used by a variety of electroactive bacteria as extracellular electron shuttles in microbial Fe reduction and inevitably interact with Fe (hydr)oxides in the extracellular environment. It is currently unknown whether flavin/Fe (hydr)oxide interaction interferes with extracellular electron transfer (EET) to the mineral surface. In this study, we found that the goethite reduction rate was lower when mediated by FMN than by RF, suggesting that FMN was less effective in shuttling electrons between cells and minerals. Nevertheless, the phosphate group did not prevent the FMN molecule from accepting electrons from bacterial cells and transferring electrons to the mineral. Results of adsorption experiment, attenuated total reflectance (ATR) Fourier transform infrared (FTIR) spectroscopy and bacterial attachment trend analyses showed that FMN exhibited strong adsorption on goethite surface by forming phosphate inner-sphere complex, which prevented bacterial cells from approaching goethite. Therefore, the interaction between FMN and goethite surface may increase the distance of electron transfer from bacterial cells to goethite and result in lower EET efficiency in comparison to those mediated by riboflavin. To our knowledge, these data reveal for the first time that the interaction between flavin and Fe (hydr)oxide affect flavin-mediated electron transfer to mineral surface, and add a new dimension to our understanding of flavin-mediated microbial Fe reduction processes.